Haikyu!!. 6, Setter battle! - Furudate, Haruichi, 1983- (Shonen Jump manga., 2016)
Kageyama and Karasuno claimed victory in the practice match, but the real game approaches, and tensions are high when Tohru Oikawa arrives on the scene.